Weight change in patients under treatment with antidepressants: A narrative review (Research, Society and Development, 2022)
Antidepressants are used in the treatment of several pathologies with a high incidence and prevalence. However, they are associated with several side effects, such as weight gain or loss. Thus, the objective of this study was to elaborate a narrative review about the change in body weight caused by antidepressants, as well as the possible biopsychosocial consequences of this. For this purpose, scientific articles, books and bulletins from the Ministry of Health were consulted. Studies indicated that antidepressants differ in terms of the possibility of causing weight change, in addition to the existence of multiple factors which may interfere in the expression of these effects. Furthermore, not all antidepressants of the same class promote weight change following the same pattern. Thus, in the initial treatment period, they can cause weight gain, loss or no change at all. However, in the long term, the majority seem to cause weight gain, including certain selective serotonin reuptake inhibitors, a fact unknown to some people who use them for weight loss. Bupropion was the only antidepressant shown to significantly contribute to weight loss, even during long-term treatment. It was also found that weight gain might influence treatment abandonment, which in turn can lead to relapses and/or worsening of the underlying pathology. In contrast, indiscriminate use aimed at weight loss can interfere with mood, well-being, and behaviour. In view of the aforementioned, it is important that physicians have up-to-date knowledge on the subject, in order to properly prescribe medications and correctly advise their patients.